The Influence of Different Acupuncture Manipulations on the Skin Temperature of an Acupoint. (13th February 2013) - Huang, Tao; Huang, Xin; Zhang, Weibo; Jia, Shuyong; Cheng, Xinnong; Litscher, Gerhard
Abstract : This study was performed to observe the influence of sham and different verum acupuncture manipulations on skin temperature of the stimulated acupoint in healthy volunteers. Thirty-seven healthy volunteers with a mean age of 25.4 ± 2.2 years were enrolled in the study. All volunteers had experienced acupuncture before. They received sham acupuncture and two different kinds of verum acupuncture stimulation (lifting-thrusting and twisting-rotating) on Zusanli (ST36). The skin temperature of ST36 was measured before acupuncture, after needle insertion, after needle manipulation, immediately after removal of the needle, and as further control 5 minutes after removal of the needle using a FLIR i7 infrared thermal camera. During the measurement, the needling sensations of volunteers were enquired and recorded. During the sham acupuncture stimulation, the skin temperature of ST36 decreased in the first 5 minutes, when the point was exposed, and then increased gradually. During verum acupuncture stimulations, the skin temperature increased continually and then decreased in the last phase. The increase in temperature caused by lifting-thrusting stimulation was significantly higher than that of twisting-rotating manipulation, which may be related to the stimulation intensity.